Exercises following anterior cruciate ligament reconstructive surgery: Biomechanical considerations and efficacy of current approaches - Grodski, M.; Marks, R. (Research in Sports Medicine, 2008)
To enable a safe, effective return to daily functional activities and to prevent premature knee joint osteoarthritis, adults undergoing anterior cruciate ligament (ACL) surgery require carefully designed and appropriate rehabilitation strategies. In this article we critically examine the contemporary body of literature concerning the application and outcomes of various knee exercise rehabilitation protocols described in the literature in the context of the surgically repaired ACL injured knee. These data were obtained from the MEDLINE (1991-2007), CINAHL (1982-2007), and SPORTS DISCUS (1975-2007) databases, using the terms anterior cruciate ligament, exercise, and ligament, showed that two lines of research currently dominate this topic: (1) the role of open versus closed chain exercises approaches; (2) the impact of these exercises on knee stability and function post-ACL surgery. In light of the small number of studies and their methodological limitations, however, more research clearly is recommended to establish if closed-chain kinetic exercises are conclusively more efficacious than open-chain exercise for this condition, as predicted by the present literature base.